(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: The assessment is an integral part of the clinical teaching-learning process in undergraduate medical education. Methods: This cross-sectional study was conducted to identify the views of fresh MBBS graduates about the present assessment status of ’Allied Subjects of Surgery’ in undergraduate medical education in Bangladesh. The study was conducted from January 2021 to December 2021. Self-administered semi-structured questionnaires were administered to collect data from 40 fresh MBBS graduates. Data were collected from purposively selected 40 fresh MBBS graduates who passed the MBBS course with the completion of internship training within five years working in government and private hospitals or giving health care services in their chamber after getting permission from the respondents. Results: This Study revealed that the conditions of different issues like formative assessments, summative assessments (Professional examinations), short answer questions (SAQ), multiple choice questions (MCQ), structured oral examinations (SOE), objective structured clinical examinations (OSCE) and short cases were poor and in case of long cases were very poor in most of the Allied Subjects of Surgery compared to General Surgery, Otolaryngology and Ophthalmology. These differences were also statistically highly significant in all cases. Conclusion: Hence it can be recommended that most of the Allied Subjects of Surgery should get optimum importance during the assessment procedures in undergraduate medical education of Bangladesh according to the health needs of the community and current global health care situation. TAJ 2022; 35: No-2: 27-33